Morcellating uterine mesenchymal tumors: The pathologist's view. Issue 3 (25th January 2017) - Pavlakis, Kitty; Messini, Irini; Yiannou, Petros; Gavresea, Theofani; Chrysanthakis, Dimitris; Hilaris, Georgios; Panoskaltsis, Theodoros
Abstract: Aim: The study was conducted to delineate the histological problems in diagnosing uterine mesenchymal tumors in morcellated material. Methods: All cases of morcellated uteri performed between 2008 and 2014 were reviewed. The incidence of unexpected malignancy, defined as any neoplasm with a clear‐cut diagnosis of leiomyosarcoma (LMS) or endometrial stromal sarcoma (ESS), was noted. Cases with absolute discrepancy between the diagnosis of the morcellated tumor and the subsequent diagnosis were also included in the study. Results: Out of 631 cases, a final diagnosis of LMS or ESS was made regarding three and five tumors, respectively. Patient age ranged from 25 to 48 years. Two further cases initially diagnosed as ESS proved to be endometrial stromal nodules with smooth muscle differentiation. Two cases were diagnosed as smooth muscle tumors with uncertain malignant potential and the patients remain free of disease. One tumor was diagnosed as an endometrial stromal neoplasm and proved to be benign and finally a leiomyoma variant presented with presumed peritoneal disease. Conclusion: Both endometrial stromal and smooth muscle tumors with malignant behavior can be encountered at a young age. Because of the limitations in histological evaluation, morcellated tumors may be overdiagnosed or underdiagnosed by pathologists.